A Study of Telecommunication Policies and Broadband Penetration for Sweden and South Korea - Nabaz T. Khayyat (UKH Journal of Science and Engineering, 2017)
Internet broadband technology is the next phase in internet evolution. The emergence of broadband brought many options to internet users. It is evident that in the future, broadband Internet may introduce a big difference in the lives of the public, industry, and the government. However, the diffusion of Broadband is clogged at the regulation crossroads between market, government, and consumer, especially with regard to allow third parties to be involved in building the broadband infrastructure. Controlling access to the development of broadband infrastructure may produce a monopolizing market and limiting the variety and quality of available services. The current study investigates the development of broadband and its penetration in South Korea (the highest country with the access to broadband services), and Sweden (the second highest rate of internet penetration among the OECD countries). The paper overviews the broadband markets in both countries, focusing on their government policies in promoting the technology used and the growth of the market. The paper argues about the challenges facing the market for developing broadband technology, such as increase in the demand and supply for higher speed broadband, increase in the traffic congestion as users spend more time using internet and more data are transferred between individual, software, and applications, etc. the paper finally derives a number of ICT policy objectives and classifies the two countries based on their market approach into: laissez faire (free markets) and markets led by the government’s national plan, with quantified objectives and the regulators instruments strategies to meet the mentioned objectives.